Ramadan fasting in people with adrenal insufficiency: Risk assessment and management - Morshed, Md Shahed; Mohana, Choman Abdullah (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Fasting during Ramadan predisposes patients with adrenal insufficiency (AI) to adrenal crisis. If patients with AI intend to fast, physicians should respect the patient's wish and assist them in safely performing their religious activities. Evidence-based management for AI is limited and mostly based on expert opinions. This mini-review summarizes the guidelines and current evidence to help physicians and patients manging AI during Ramadan fasting. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2025;4(1): 31-33